If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 63 = 9z Solving 63 = 9z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-9z' to each side of the equation. 63 + -9z = 9z + -9z Combine like terms: 9z + -9z = 0 63 + -9z = 0 Add '-63' to each side of the equation. 63 + -63 + -9z = 0 + -63 Combine like terms: 63 + -63 = 0 0 + -9z = 0 + -63 -9z = 0 + -63 Combine like terms: 0 + -63 = -63 -9z = -63 Divide each side by '-9'. z = 7 Simplifying z = 7
| 13-9h-15=7h+22-8h | | 2(4n-11)+8=5n+4 | | 82=12m | | 3*s=330 | | 3(t-4)=5(t+1)-1 | | 2x=4(x+3) | | -12x=-120 | | 45x^2+20x=45x+20 | | -16=-25-x | | 6p+p=7p | | -5/8w+2/5=-7/8w+1/8 | | 5x^2+x-328=0 | | -7=-10+x | | X^2+11x+35=5 | | 8P^4*3p= | | 25x-5+10x= | | 2x^4-4x^3-3=0 | | 3-2/2+6=z+8 | | X^2+42X-43=0 | | 7-3x=x-4(2+6) | | b+3=33-b | | 3-9=4x+4 | | x=250+0.8(x-(325+0.25x))+650-80i+560 | | 1x^2-30x=0 | | 6x^2-5x=x | | 4x-12=24+8x | | 11x+12y=150 | | (x^2+7x-48)/(x+9) | | 6x-3(x-4)=2(x+7)+x | | p^2-13p+36=0 | | 4x+16=-12 | | 10-2x=9-5x |